The Legal Framework for Managing Public Facilities by Electronic Means - Hussein, Dr. Mustafa Rasool (Journal of Legal and Political Studies, 2019)
E. Management anew and radical transformation aims to reinvent government performance itself again to provide government services to citizens better and with high accuracy and less effort and with out need to waiting long lines and what was this new system depends on the style of a science and technology, anew measure to get rid of negative abd disadvantages of performance government.it is nesessary to keep pace with this development of government administration and if the e-management requires numerous requirements, the legal framework is one of more of these requirements and imporance of accuracy construction.
Keywords: radical transformation; E Management; legal framework; accuracy construction